Immune-pathological response induced by Saprolegnia parasitica in Pangasianodon hypophthalmus and assessment of clinical efficacy of clotrimazole - Sanjaykumar Karsanbhai Rathod; Sanjib Kumar Manna; Asit Kumar Bera; Samikshya Mishra; Sohini Chatterjee; Gayatri Tripathi; Bhautik D. Savaliya; Saurav Kumar (Brazilian Journal of Microbiology, 2026)

Corrigendum to ‘A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management’ [Earth-Science Reviews 278 (2026) 1-28] - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

Superheated non-catalytic transesterification of binary mixture of Madhuca indica and waste cooking oil towards biodiesel synthesis - Bisheswar Karmakar; Rishya Prava Chatterjee; D. Rhithuparna; Sankha Chakrabortty; Rashid Imran Ahmad Khan; Gopinath Halder (Biomass and Bioenergy, 2026)

Performance assessment of transformer-based model for Sea Surface Temperature Prediction in the Indian Ocean Region - D. Sathya Narayanan; B. Sheela Rani; N.R. Krishnamoorthy; M. Roja Raman; V. Kalyan; Aneesh A. Lotliker; Abhisek Chatterjee (Regional Studies in Marine Science, 2026)

Machine Learning-based Prediction and Optimization of Photocatalytic Degradation of Methylene Blue Using TiO₂, Fe₂O₃, and Ti–Fe Composite Nanomaterials - Sweety Khut; Aajinkya Singh; Arpan Chatterjee; Ankush B. Bindwal; Pravin D. Patil; Shamraja S. Nadar; Manishkumar S. Tiwari (Environmental Processes, 2026)

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Deep learning for sea surface temperature prediction in the Indian Ocean: A comparative study using 1D-CNN, LSTM, 1DCNN-LSTM and attention based 1DCNN-LSTM architectures - B. Sheela Rani; D. Sathya Narayanan; M.B. Salma Jasmine; N.R. Krishnamoorthy; M. Roja Raman; Aneesh A. Lotliker; Abhisek Chatterjee (Dynamics of Atmospheres and Oceans, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Beyond the target: the ecotoxicological impact of flubendiamide in natural ecosystems - T. Roy; S. Ghosh; A. H. Mandal; N. C. Saha; S. Chatterjee; D. S. Paria; C. R. Multisanti; C. Faggio; S. Saha (International Journal of Environmental Science and Technology, 2026)

Surface engineered CeMnOx@DHNS core-shell nanostructures as multifunctional additives for highly durable proton exchange membranes - Sk Miraz Hossain; Pratyush Patnaik; Santoshkumar D. Bhat; Uma Chatterjee (Chemical Engineering Journal, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Characterization of Composite Agarose–Collagen Hydrogels for Chondrocyte Culture - Clarisse Zigan; Claudia Benito Alston; Aritra Chatterjee; Luis Solorio; Deva D. Chan (Annals of Biomedical Engineering, 2025)
To elucidate the mechanisms of cellular mechanotransduction, it is necessary to employ biomaterials that effectively merge biofunctionality with appropriate mechanical characteristics. Agarose and collagen separately are common biopolymers used in cartilage mechanobiology and mechanotransduction studies but lack features that make them ideal for functional engineered cartilage. In this study, agarose is blended with collagen type I to create hydrogels with final concentrations of 4% w/v or 2% w/v agarose with 2 mg/mL collagen. We hypothesized that the addition of collagen into a high-concentration agarose hydrogel does not diminish mechanical properties. Acellular and cell-laden studies were completed to assess rheologic and compressive properties, contraction, and structural homogeneity in addition to cell proliferation and sulfated glycosaminoglycan production. Over 21 days in culture, cellular 4% agarose–2 mg/mL collagen I hydrogels seeded with primary murine chondrocytes displayed structural and bulk mechanical behaviors that did not significantly alter from 4% agarose-only hydrogels, cell proliferation, and continual glycosaminoglycan production, indicating promise toward the development of an effective hydrogel for chondrocyte mechanotransduction and mechanobiology studies.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Genetic manipulation of Indian mustard genotypes with WRR-gene(s) confers resistance against Albugo candida - Shradha Nirwan; Anupriya Chatterjee; Volkan Cevik; Eric B. Holub; Jonathan D. G. Jones; Anand Kumar Tewari; Neeraj Shrivastava; Abha Agnihotri; Pankaj Sharma (Molecular Biology Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cycling of fluid-mobile elements through the forearc: Insights from the Cl, B, and Li isotope composition of Costa Rican spring fluids - Jacob P. Helper; Jaime D. Barnes; J. Maarten de Moor; Alejandro Rodríguez; Samuele Agostini; George Segee-Wright; Rudra Chatterjee; Daniel F. Stockli (Geochimica et Cosmochimica Acta, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

A carbon dots-MnO2 nanosheet-based turn-on pseudochemodosimeter as low-cost probe for selective detection of hazardous mercury ion contaminations in water - Ankit Thakuri; Akhil A. Bhosle; Sharanabasava D. Hiremath; Mainak Banerjee; Amrita Chatterjee (Journal of Hazardous Materials, 2024)

Potential of nano-phytoremediation of heavy metal contaminated soil: emphasizing the role of mycorrhizal fungi in the amelioration process - A. Mitra; S. Kataki; S. Chatterjee; D. K. Gupta (International Journal of Environmental Science and Technology, 2024)

A review on environmental impacts of renewable energy for sustainable development - D. Gayen; R. Chatterjee; S. Roy (International Journal of Environmental Science and Technology, 2024)

Reconnaissance to characterisation of land subsidence due to groundwater overdraft and oil extraction in and around Mehsana City, Gujarat, India by long-term hybrid differential interferometric SAR technique - R.S. Chatterjee; Shravanee Singha; Ashish Aggarwal; Vimanyu Sharma; Pranshu Pranjal; Anuradha Karunakalage; P.K. Jain; A. Nagar; D.S. Mitra; D. Kumar; N.R. Patel; P. Chauhan (Journal of Hydrology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

The nickel output to abyssal pelagic manganese oxides: A balanced elemental and isotope budget for the oceans - Sarah Fleischmann; Jianghui Du; Aditi Chatterjee; James McManus; Sridhar D. Iyer; Ankeeta Amonkar; Derek Vance (Earth and Planetary Science Letters, 2023)

Lichens as spatially transferable bioindicators for monitoring nitrogen pollution - Jay Delves; Jason E.J. Lewis; Niaz Ali; Saeed A. Asad; Sudipto Chatterjee; Peter D. Crittenden; Matthew Jones; Aysha Kiran; Bishnu Prasad Pandey; David Reay; Subodh Sharma; Dendup Tshering; et al. (Environmental Pollution, 2023)

Halogen enrichment in the North American lithospheric mantle from the dehydration of the Farallon plate - George Segee-Wright; Jaime D. Barnes; John C. Lassiter; Duncan J. Holmes; Grace M. Beaudoin; Rudra Chatterjee; Daniel F. Stockli; J. Elis Hoffmann; Timm John (Geochimica et Cosmochimica Acta, 2023)

Agronomic manipulation in main season and ratoon rice influences growth, productivity, and regeneration ability in tropical lowlands - B. Lal; Priyanka Gautam; A.K. Nayak; R. Raja; B.B. Panda; R. Tripathi; M. Shahid; D. Chatterjee; P. Bhattacharyya; P. Bihari; Teekam Singh; S.K. Meena; et al. (Field Crops Research, 2023)

Hydrated komatiites as a source of water for TTG formation in the Archean - R. Tamblyn; J. Hermann; D. Hasterok; P. Sossi; T. Pettke; S. Chatterjee (Earth and Planetary Science Letters, 2023)

Spotlight on the spot market: A review of the indian wholesale electricity market - D. Chattopadhyay; S.K. Chatterjee; S.K. Soonee (The Electricity Journal, 2023)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Agricultural GHG emission and calorie intake nexus among different socioeconomic households of rural eastern India - Rahul Tripathi; B. Dhal; Md Shahid; S. K. Barik; A. D. Nayak; B. Mondal; S. D. Mohapatra; D. Chatterjee; B. Lal; Priyanka Gautam; N. N. Jambhulkar; Nuala Fitton; et al. (Environment, Development and Sustainability, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Current understanding of the surface contamination and contact transmission of SARS-CoV-2 in healthcare settings - Hosoon Choi; Piyali Chatterjee; John D. Coppin; Julie A. Martel; Munok Hwang; Chetan Jinadatha; Virender K. Sharma (Environmental Chemistry Letters, 2021)

Forest data visualization and land mapping using support vector machines and decision trees - Sujatha Radhakrishnan; Aarthy Seshadri Lakshminarayanan; Jyotir Moy Chatterjee; D. Jude Hemanth (Earth Science Informatics, 2020)

Effect of reducing energy intake during the dry period on milk production, udder health, and body condition score of Jersey crossbred cows in the tropical lower Gangetic region - Amit Kumar Singh; Champak Bhakat; D. K. Mandal; A. Mandal; S. Rai; A. Chatterjee; M. K. Ghosh (Tropical Animal Health and Production, 2020)

Effects of integrated farming system and rainwater harvesting on livelihood improvement in North-Eastern region of India compared to traditional shifting cultivation: evidence from an action research - Sanjay Kumar Ray; Dibyendu Chatterjee; D. J. Rajkhowa; S. K. Baishya; S. Hazarika; S. Paul (Agroforestry Systems, 2020)

Depth-wise distribution of soil-carbon stock in aggregate-sized fractions under shaded-perennial agroforestry systems in the Western Ghats of Karnataka, India - Nilovna Chatterjee; P. K. Ramachandran Nair; Vimala D. Nair; Syam Viswanath; Abhishek Bhattacharjee (Agroforestry Systems, 2020)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

A RNAscope whole mount approach that can be combined with immunofluorescence to quantify differential distribution of mRNA - Jennifer Kersigo; Ning Pan; Joseph D. Lederman; Snehajyoti Chatterjee; Ted Abel; Gabriela Pavlinkova; Immaculada Silos-Santiago; Bernd Fritzsch (Cell and Tissue Research, 2018)

A Chemosensitizer Drug: Disulfiram Prevents Doxorubicin-Induced Cardiac Dysfunction and Oxidative Stress in Rats - Varsha K. Sonawane; Umesh B. Mahajan; Sachin D. Shinde; Subhajit Chatterjee; Sandip S. Chaudhari; Harshada A. Bhangale; Shreesh Ojha; Sameer N. Goyal; Chanakya N. Kundu; Chandragouda R. Patil (Cardiovascular Toxicology, 2018)

Numerical simulation of the observed near-surface East India Coastal Current on the continental slope - A. Mukherjee; D. Shankar; Abhisek Chatterjee; P. N. Vinayachandran (Climate Dynamics, 2018)

Evaluation of the oncolytic potential of R2B Mukteshwar vaccine strain of Newcastle disease virus (NDV) in a colon cancer cell line (SW-620) - Kishan K. Sharma; Irsadullakhan H. Kalyani; Jogeswar Mohapatra; Satish D. Patel; Dharmesh R. Patel; Priti D. Vihol; Abhijit Chatterjee; Dinesh R. Patel; Bhavesh Vyas (Archives of Virology, 2017)

Erratum to: Inhibition of mixed-layer deepening during winter in the northeastern Arabian Sea by the West India Coastal Current - D. Shankar; R. Remya; P. N. Vinayachandran; Abhisek Chatterjee; Ambica Behera (Climate Dynamics, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Inhibition of mixed-layer deepening during winter in the northeastern Arabian Sea by the West India Coastal Current - D. Shankar; R. Remya; P. N. Vinayachandran; Abhisek Chatterjee; Ambica Behera (Climate Dynamics, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Variation of Stable Carbon and Nitrogen Isotopic Composition of PM10 at Urban Sites of Indo Gangetic Plain (IGP) of India - S. K. Sharma; T. K. Mandal; D. M. Shenoy; Pratirupa Bardhan; Manoj K. Srivastava; A. Chatterjee; Mohit Saxena; Saraswati; B. P. Singh; S. K. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2015)

Measurement of Vanadium Emissions from SCR Catalysts by ICP-OES: Method Development and First Results - T. J. Schildhauer; M. Elsener; J. Moser; I. Begsteiger; D. Chatterjee; K. Rusch; O. Kröcher (Emission Control Science and Technology, 2015)

Modernizing Pharmaceutical Manufacturing: from Batch to Continuous Production - Sau L. Lee; Thomas F. O’Connor; Xiaochuan Yang; Celia N. Cruz; Sharmista Chatterjee; Rapti D. Madurawe; Christine M. V. Moore; Lawrence X. Yu; Janet Woodcock (Journal of Pharmaceutical Innovation, 2015)

Interaction of NO x Reduction and Soot Oxidation in a DPF with Cu-Zeolite SCR Coating - E. Tronconi; I. Nova; F. Marchitti; G. Koltsakis; D. Karamitros; B. Maletic; N. Markert; D. Chatterjee; M. Hehle (Emission Control Science and Technology, 2015)

Tipping off endothelial tubes: nitric oxide drives tip cells - Mani Krishna Priya; Giriraj Sahu; David R. Soto-Pantoja; Naga Goldy; Abaya Meenakshi Sundaresan; Vivek Jadhav; T. R. Barathkumar; Uttara Saran; B. M. Jaffar Ali; David D. Roberts; Amal Kanti Bera; Suvro Chatterjee (Angiogenesis, 2015)

The Association of Respiratory Symptoms and Indoor Housing Conditions Among Migrant Farmworkers in Eastern North Carolina - Gregory D. Kearney; Arjun B. Chatterjee; Jennifer Talton; Haiying Chen; Sara A. Quandt; Phillip Summers; Thomas A. Arcury (Journal of Agromedicine, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Human urothelial micronucleus assay to assess genotoxic recovery by reduction of arsenic in drinking water: a cohort study in West Bengal, India - Somnath Paul; Pritha Bhattacharjee; Prafulla K. Mishra; Debmita Chatterjee; Anirban Biswas; Debasree Deb; Aloke Ghosh; D. N. Guha Mazumder; Ashok K. Giri (BioMetals, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

A new atlas of temperature and salinity for the North Indian Ocean - A CHATTERJEE; D SHANKAR; S S C SHENOI; G V REDDY; G S MICHAEL; M RAVICHANDRAN; V V GOPALKRISHNA; E P RAMA RAO; T V S UDAYA BHASKAR; V N SANJEEVAN (Journal of Earth System Science, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Quantification and Source Identification of Polycyclic Aromatic Hydrocarbons in Core Sediments from Sundarban Mangrove Wetland, India - C. Domínguez; S. K. Sarkar; A. Bhattacharya; M. Chatterjee; B. D. Bhattacharya; E. Jover; J. Albaigés; J. M. Bayona; Md. A. Alam; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2010)

Acid leachable trace metals in sediment cores from Sunderban Mangrove Wetland, India: an approach towards regular monitoring - M. P. Jonathan; S. K. Sarkar; P. D. Roy; Md. A. Alam; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; K. K. Satpathy (Ecotoxicology, 2010)

Polycyclic Aromatic Hydrocarbons in Intertidal Marine Bivalves of Sunderban Mangrove Wetland, India: An Approach to Bioindicator Species - O. Zuloaga; A. Prieto; A. Usobiaga; S. K. Sarkar; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; Md. A. Alam; K. K. Satpathy (Water, Air, & Soil Pollution, 2009)

Mixing ratios of carbonyls and BTEX in ambient air of Kolkata, India and their associated health risk - C. Dutta; D. Som; A. Chatterjee; A. K. Mukherjee; T. K. Jana; S. Sen (Environmental Monitoring and Assessment, 2009)

Organochlorine Pesticide Residues in Sediment Cores of Sunderban Wetland, Northeastern Part of Bay of Bengal, India, and Their Ecotoxicological Significance - S. K. Sarkar; A. Binelli; C. Riva; M. Parolini; M. Chatterjee; A. K. Bhattacharya; B. D. Bhattacharya; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2008)

An Assessment of Mercury Loading in Core Sediments of Sunderban Mangrove Wetland, India (A Preliminary Report) - Ž. Kwokal; S. K. Sarkar; M. Chatterjee; S. Franciskovis-Bilinski; H. Bilinski; A. Bhattacharya; B. D. Bhattacharya; Md. Aftab Alam (Bulletin of Environmental Contamination and Toxicology, 2008)

Phytotoxic Effect of Coal Mine Effluent on Growth Behavior, Betabolic Changes, and Metal Accumulation in Rice Plants (Oryza sativa L.) c.v. IR-36 - K. K. Tiwari; S. Dwivedi; U. N. Rai; A. K. Pandey; C. Chatterjee; N. K. Singh; R. D. Tripathi (Bulletin of Environmental Contamination and Toxicology, 2006)

New temperate DNA phage BcP15 acts as a drug resistance vector - D. K. Hens; N. C. Chatterjee; R. Kumar (Archives of Virology, 2006)

Silica and volatile-element metasomatism of Archean mantle: a xenolith-scale example from the Kaapvaal Craton - D. R. Bell; M. Grégoire; T. L. Grove; N. Chatterjee; R. W. Carlson; P. R. Buseck (Contributions to Mineralogy and Petrology, 2005)

A Breadth Averaged Numerical Model for Suspended Sediment Transport in Hooghly Estuary, East Coast of India - P. C. Sinha; Pragya Guliani; G. K. Jena; A. D. Rao; S. K. Dube; A. K. Chatterjee; Tad Murty (Natural Hazards, 2004)

Key site variables governing the functional characteristics of Dissolved Natural Organic Matter (DNOM) in Nordic forested catchments - Bimal Chatterjee; Egil Gjessing; Jussi V. K. Kukkonen; Hkon E. Larsen; Jrg Luster; Andrea Paul; Stephan Pflugmacher; Mike Starr; Christian E. W. Steinberg; Philippe Schmitt-Kopplin; dm Zsolnay; Rolf D. Vogt; et al. (Aquatic Sciences, 2004)

Chemical and isotopic (Pb, Sr) zonation in a peraluminous granite pluton: role of fluid fractionation - J. Dostal; A. K. Chatterjee; D. J. Kontak (Contributions to Mineralogy and Petrology, 2004)

Development of Regional Flood Frequency Relationships Using L-moments for Middle Ganga Plains Subzone 1(f) of India - Rakesh Kumar; C. Chatterjee; Sanjay Kumar; A. K. Lohani; R. D. Singh (Water Resources Management, 2003)

Sensitivity Analysis of the GIUH based Clark Model for a Catchment - Rakesh Kumar; C. Chatterjee; A. K. Lohani; Sanjay Kumar; R. D. Singh (Water Resources Management, 2002)

An Outbreak of Gangrenous Syndrome among Buffaloes and Cattle in West Bengal: Clinicopathological Studies - A. Sikdar; G.C. Chakraborty; D. Bhattacharya; S. Bakshi; D.K. Basak; A. Chatterjee; S.K. Halder (Tropical Animal Health and Production, 2000)

Effect of high altitude on sensitivity to the taste of phenylthiocarbamide - S. B. Singh; A. Chatterjee; U. Panjwani; D. K. Yadav; W. Selvamurthy; K. N. Sharma (International Journal of Biometeorology, 2000)

Gravity-directed calcium current in germinating spores of Ceratopteris richardii - Ani Chatterjee; D. Marshall Porterfield; Peter S. Smith; Stanley J. Roux (Planta, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A thermodynamic analysis of the system LiAlSiO4-NaAlSiO4-Al2O3-SiO2-H2O based on new heat capacity, thermal expansion, and compressibility data for selected phases - Detlef W. Fasshauer; Niranjan D. Chatterjee; Ladislav Cemic (Contributions to Mineralogy and Petrology, 1998)

The Bayesian approach to an internally consistent thermodynamic database: theory, database, and generation of phase diagrams - Niranjan D. Chatterjee; Ralf Krüger; Gerd Haller; Walter Olbricht (Contributions to Mineralogy and Petrology, 1998)

Dynamical Initialization of Boundary-Layer Data - G. K. Sen; M. Chatterjee; D. K. Sinha (Boundary-Layer Meteorology, 1998)

Heat capacity of wadeite-type K 2 Si 4 O 9 and the pressure-induced stable decomposition of K-feldspar - Detlef W. Fasshauer; Bernd Wunder; Niranjan D. Chatterjee; Günther W. H. Höhne (Contributions to Mineralogy and Petrology, 1998)

Mildly alkaline basalts from Pavagadh Hill, India: Deccan flood basalts with an asthenospheric origin - J. D. Greenough; K. R. Hari; A. C. Chatterjee; M. Santosh (Mineralogy and Petrology, 1998)

Synthesis, structure, thermodynamic properties, and stability relations of K-cymrite, K[AlSi 3 O 8 ]·H 2 O - Detlef W. Fasshauer; Niranjan D. Chatterjee; Bernd Marler (Physics and Chemistry of Minerals, 1997)

Zinc and iron as bioindicators of precancerous nature of oral submucuos fibrosis - R. R. Paul; J. Chatterjee; A. K. Das; S. K. Dutta; D. Roy (Biological Trace Element Research, 1996)